Ovarian malignancies and polyneoplasias: clinical presentation, diagnosis, mechanisms of development, prognosis - P. Z. Kutalia; V. Yu. Selchuk; Yu. G. Payanidi; K. I. Zhordania; V. M. Shelepova; T. I. Zakharova (Опухоли женской репродуктивной системы, 2014)
The paper considers the clinical picture, diagnosis, mechanisms of development, and prognosis of ovarian malignancies and polyneoplasias in detail. The purpose of the investigation was to study the clinical features of polyneoplasms with the involvement of the ovaries and to define the ways of improving their diagnosis.